On the size and composition of particles in polar stratospheric clouds - Browell, Edward V.; Toon, Goeff C.; Farmer, Crofton B.; Toon, Owen B.; Kinne, Stefan (1988)
Attenuation measurements of the solar radiation between 1.5 and 15 micron wavelengths were performed with the airborne (DC-8) JPL MARK 4 interferometer during the 1987 Antarctic Expedition. The opacities not only provide information about the abundance of stratospheric gases but also about the optical depths of polar stratospheric clouds (PSCs) at wavelengths of negligible gas absorption (windows). The optical depth of PSCs can be determined for each window once the background attenuation, due to air-molecules and aerosol has been filtered out with a simple extinction law. The ratio of optical thicknesses at different wavelengths reveals information about particle size and particle composition. Among the almost 700 measured spectra only a few PSC cases exist. PSC events are identified by sudden reductions in the spectrally integrated intensity value and are also verified with backscattering data from an upward directed lidar instrument, that was mounted on the DC-8. For the selected case on September 21st at 14.40 GMT, lidar data indicate an optically thin cloud at 18k and later an additional optically thick cloud at 15 km altitude. All results still suffer from: (1) often arbitrary definitions of a clear case, that often already may have contained PSC particles and (2) noise problems that restrict the calculations of optical depths to values larger than 0.001. Once these problems are handled, this instrument may become a valuable tool towards a better understanding of the role PSCs play in the Antarctic stratosphere.